International Survey about Perceptions of Courts’ Role in Addressing Social Issues through Problem-Solving Courts - Cunius, M. Katie; Miller, Monica K.; Murphy, Evan; Kruger, Sarah A. (Frontiers in Law, 2025)
Purpose of the study: Community sentiment is a collective group of attitudes toward an object–such as problem-solving courts–which could differ between populations. This study addresses community sentiment regarding whether the courts should address social problems and whether community sentiment differs based on the type of problem-solving court. It also investigates whether the perceived responsibility of courts to address social issues differs based on country (United States, Australia, and Canada) or individual differences, as well as whether group or individual differences are more predictive of support for problem-solving courts. Method: We surveyed citizens in the U.S., Australia, and Canada using an online survey. Results: We found that participants had positive community sentiment toward all four (drug, homelessness, mental health, tribal wellness/Aboriginal) problem-solving courts and community sentiment did not differ between countries. We also found that endorsement of therapeutic jurisprudence was the largest predictor for community sentiment toward all four courts. Conclusion: We found that sentiment was positive but similar in all countries. Individual differences (e.g., authoritarianism, support for justice principles, and attributions for crime) were stronger predictors than country of residence. This study can help encourage the creation of specialty courts to address social issues.